The Influence Of Taxpayer's Understanding And Knowledge About Tax Regulations, Quality Of Services And Tax Sanctions On Motor Vehicle Taxpayer Compliance In Lebong District (Empirical Study At Samsat Lebong Regency) - Ahmad Junaidi; Dieago Setya Pratama (Penerbit Jurnal Indonesia, 2023)
This study entitled The Effect of Understanding and Knowledge of Taxpayers on Tax Regulations, Quality of Service and Tax Sanctions on Compliance of Motorized Vehicle Taxpayers in Lebong Regency (Empirical Study at SAMSAT Lebong Regency). The background of the problem in this study is the low level of taxpayer compliance. The purpose of this study was to examine the effect of understanding and knowledge of taxpayers about tax regulations, service quality and tax penalties on motor vehicle taxpayer compliance. This type of research includes quantitative descriptive research.The population in this study are taxpayers in Lebong Regency, while the number of taxpayers for two-wheeled motorized vehicles in Lebong Regency is 9,347. The method used in selecting the sample is based on the Taro Yamane formula. Of the 99 questionnaires distributed, only 99 questionnaires were processed. The results of the hypothesis test for the variable Understanding and Knowledge of Taxes t test have a significance level of 0.000, which means <0.05. This shows that this research supports the first hypothesis (H1 is accepted). 0.000, which means <0.05 This shows that this study supports the first hypothesis (H2 is accepted). The results of the hypothesis test for the Tax Sanctions variable in the t test have a significance level of 0.000, which means <0.05. supports the third hypothesis (H3 is accepted). Accountability Report, Quality of Service and Tax Sanctions that is equal to 98.6%. while the remaining 1.4% is explained by other variables not included in this study, such as transparency, government performance, competence of village officials, and others.